Identification and Ranking of the Dimensions of Organizational Transparency with a Cognitive Approach at Mazandaran University of Medical Sciences - Ghadiri , Ramin; Yousefi Saeedabadi, Reza; Salehi , Mohammad (Assessment and Practice in Educational Sciences, 2024)
ABSTRACTOrganizational transparency is recognized as one of the fundamental principles of effective and efficient organizational management. The overall aim of the present study was to identify and rank the dimensions of organizational transparency with a cognitive approach at Mazandaran University of Medical Sciences. In terms of purpose, the study was applied, and in terms of data type, it adopted a mixed-methods (qualitative–quantitative) exploratory design. In the qualitative phase, the grounded theory method was employed, and in the quantitative phase, a descriptive–survey approach was used. The statistical population in the qualitative phase consisted of university professors and experts, as well as experienced administrators of Mazandaran University of Medical Sciences (n = 25), and in the quantitative phase, faculty members of Mazandaran University of Medical Sciences (n = 630). In the qualitative phase, 17 participants were selected using purposive non-random sampling based on the principle of theoretical saturation, and in the quantitative phase, 239 participants were selected using stratified random sampling based on Cochran’s formula. Data collection in the qualitative phase was conducted through semi-structured interviews, and in the quantitative phase through a researcher-developed questionnaire comprising 60 items. The face and content validity of the instrument were confirmed. Data analysis was performed using confirmatory factor analysis and the Friedman test. Organizational transparency with a cognitive approach at Mazandaran University of Medical Sciences comprises eight dimensions: human resource management, accountability, participation and inclusion, organizational culture, commitment to transparency, education and empowerment, information transparency, and transparency in social responsibility. The ranking of the dimensions of organizational transparency with a cognitive approach at Mazandaran University of Medical Sciences differs, such that information transparency, with a mean rank of 5.34, ranked first, while participation and inclusion, with a mean rank of 4.04, ranked last. Information transparency is one of the most important dimensions of organizational transparency with a cognitive approach at Mazandaran University of Medical Sciences and plays a vital role in creating a healthy and credible educational and research environment.